Antibacterial and Antifungal Activity of Alternantherasessilis (Linn.) R.Br.Ex DC - Saswotika Nayak; Kalpita Bhatta (International Journal of Pharma and Bio Sciences, 2020)
The aim of the present investigation was to evaluate the antimicrobial properties of Alternanthera sessilis leaves extract using two different solvents such as chloroform and methanol against Gram positive, Gram Negative Bacteria and Fungi The leaves of Alternanthera sessilis (Linn.) R.Br.ex DC (Family Amaranthaceae) were exhaustively extracted by using soxhlet apparatus. Extracts of Alternanthera sessilis were evaluated against microbial strains such as Escherichia coli (MTCC723), Staphylococcus aureus (MTCC902) and fungi Candida albicans (MTCC4748), Aspergillus fumigatus (MTCC2550) using well diffusion method. Standard such as Ciprofloxacin and Fluconazole were used for comparison. Promising antibacterial activity was observed in the methanol extract with an inhibition zone of 16mm against E. coli, 9mm against Staphylococcus aureus, 12mm against Candida albicans and14mm against Aspergillus fumigatus .Whereas chloroform extracts showed a 10mm zone of inhibition against E. coli. The results of the MIC study revealed the antimicrobial activity of the extract against the tested strains of microorganisms between concentration range of 50 to 100 μg/ml. The present study indicates the potential usefulness of Alternanthera sessilis Linn. Aerial parts in the treatment of various pathogenic diseases as mentioned in the ayurvedic literature. The extracts of leaves of Alternanthera sessilis showed antimicrobial activity due to presence of different phytochemical constituents.